An Efficient and Rapid Assay for Detecting Neutralizing Antibodies Against Serotype 4 Fowl Adenovirus - Guo, Yiwen; Xie, Songhua; Xu, Zhenqi; Xie, Quan; Wang, Weikang; Wan, Zhimin; Li, Tuofan; Qin, Aijian; Shao, Hongxia; Ye, Jianqiang (Frontiers in Veterinary Science, 2022)
Currently, the outbreak of serotype 4 fowl adenovirus (FAdV-4) has spread worldwide and caused tremendous economic loss to poultry industry. Although inactivated vaccines have been licensed against FAdV-4 in China, a rapid and efficient serological method for measuring the titer of neutralizing antibodies (NAbs) specific for FAdV-4 post infection or vaccination is rarely reported. Classical virus neutralization test (VNT) is superior in sensitivity and specificity for detecting NAbs but either time-consuming or laborious. In this study, a recombinant virus FA4-EGFP expressing EGFP-Fiber-2 fusion protein, rather than wild type (WT) FAdV-4 was used to develop a novel VNT for detecting FAdV-4 NAbs. Specificity analysis showed that the approach only reacted with the sera against FAdV-4, not with the sera against other avian pathogens tested. The novel VNT was effective in the detection of NAbs against FAdV-4 in sera from both experimentally infected and clinically vaccinated chickens, and had good linear correlation with the classical VNT. Moreover, the novel VNT not only significantly simplifies the procedure for detection of NAbs, but also shorten the time line to 24 h in comparison with the classical VNT with 3-4 days. All these data demonstrate that the FA4-EGFP based VNT developed here provides an efficient diagnostic method for monitoring the immunological state of the vaccination or diagnosing the clinical infection of FAdV-4 in a quick and funding-saving manner.